A microcosm study to support aquatic risk assessment of nickel: Community‐level effects and comparison with bioavailability‐normalized species sensitivity distributions. (18th March 2016) - Hommen, Udo; Knopf, Burkhard; Rüdel, Heinz; Schäfers, Christoph; De Schamphelaere, Karel; Schlekat, Chris; Garman, Emily Rogevich
Abstract: The aquatic risk assessment for nickel (Ni) in the European Union is based on chronic species sensitivity distributions and the use of bioavailability models. To test whether a bioavailability‐based safe threshold of Ni (the hazardous concentration for 5% of species [HC5]) is protective for aquatic communities, microcosms were exposed to 5 stable Ni treatments (6–96 μg/L) and a control for 4 mo to assess bioaccumulation and effects on phytoplankton, periphyton, zooplankton, and snails. Concentrations of Ni in the periphyton, macrophytes, and snails measured at the end of the exposure period increased in a dose‐dependent manner but did not indicate biomagnification. Abundance of phytoplankton and snails decreased in 48 μg Ni/L and 96 μg Ni/L treatments, which may have indirectly affected the abundance of zooplankton and periphyton. Exposure up to 24 μg Ni/L had no adverse effects on algae and zooplankton, whereas the rate of population decline of the snails at 24 μg Ni/L was significantly higher than in the controls. Therefore, the study‐specific overall no‐observed‐adverse‐effect concentration (NOAEC) is 12 μg Ni/L. This NOAEC is approximately twice the HC5 derived from a chronic species sensitivity distribution considering the specific water chemistry of the microcosm by means of bioavailability models. Thus, the present study provides support to the protectiveness of the bioavailability‐normalized HC5 for freshwater communities. Environ Toxicol Chem 2016;35:1172–1182. © 2015 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.